Enhancing Junior High School Students’ Reading Comprehension through Quizizz-Based Gamified Assessment - Fatimah, Siti (English Language and Literature in Education Journal, 2025)
The integration of gamified assessment tools in reading comprehension instruction remains underexplored, particularly in the context of Indonesian junior high schools. Traditional reading assessments often fail to engage students, leading to decreased motivation and suboptimal comprehension outcomes. Despite the growing adoption of digital learning platforms, limited research has examined the effectiveness of Quizizz in fostering reading comprehension among junior high school students. Addressing this gap, this study aimed to investigate the impact of Quizizz-based gamified assessment on the reading comprehension of ninth-grade students at SMP Negeri 44 Surabaya. A pre-experimental design was employed, involving 35 students from Grade IX-B. Data were collected through pre-post tests and structured interviews with five selected students. The findings revealed that the implementation of Quizizz significantly enhanced students’ ability to comprehend texts, particularly in identifying main ideas, making inferences, and understanding contextual meanings. Students exhibited increased engagement and active participation, as the game-like features of Quizizz fostered a more interactive and enjoyable learning environment. Moreover, the interview results indicated that students perceived Quizizz as a motivating and effective tool that reduced test anxiety and encouraged self-paced learning. These findings highlight the potential of gamified assessment to transform reading comprehension instruction by improving both cognitive and affective learning outcomes. The study suggests that educators integrate Quizizz strategically in reading lessons, ensuring alignment with curriculum goals and student proficiency levels. Future research could explore long-term effects, comparative studies with other gamification tools, and its impact on different reading proficiency levels.